Radioautographic and biochemical studies of secretion of venom protein in the South American rattlesnake Crotalus durissus terrificus - Marchi, F.; Haddad, A.; De Lucca, F. L. (Wiley, 1978)
Protein secretion was investigated in the main venom gland of the South American rattlesnake, using radioautographic and biochemical techniques after a single intracardiac injection of L‐(3,5‐3H)tyrosine. All the snakes were injected at the fourth day of the secretory cycle and killed at 1/2, 1, 2, 4, 8 and 24 hours after injection. Most of the radioactive amino acid is cleared from the blood stream up to four hours after injection. On the other hand the specific activity (c.p.m./mg of protein) of the intracellular proteins reaches a peak at the 4‐hour time interval decreasing aftewards. There was a good correlation between the values of the specific activity of the intracellular proteins and those of the silver grain density over the secretory cells at the several time intervals after the injection of 3H‐tyrosine. The results of the quantitative analysis carried out in light‐ and electron‐microscope radioautographs led to the conclusion that venom proteins are synthesized in the rough endoplasmic reticulum of the secretory cells, transferred to the Golgi apparatus from where they are carried to the secretory tubule lumen by the secretion granules. The fact that the values of the relative concentration of the radioactivity of the intracisternal granules double at the last three time intervals, strongly suggests that these structures are formed by the aggregation of the amorphous material present inside the cisternae of the rough endoplasmic reticulum. Copyright © 1978 Wiley‐Liss, Inc., A Wiley Company